The impact of road roughness on the duration of contact between a vehicle wheel and road surface - Žuraulis, Vidas; Levulytė, Loreta; Sokolovskij, Edgar (Transport, 2014)
The paper analyses the impact of the road micro-profile on the duration and the type of the vehicle wheel contact with the road surface driving at different speed. The selected vehicle bicycle model describes vertical displacements of front and rear wheels and their suspension as well as the impact of the vehicle body motion and longitudinal oscillation. International Roughness Index (IRI) and micro-profile irregularities of the road section analysed in the paper were identified using specialized road testing equipment. The experimental investigations measuring the vehicle suspension displacement and the body acceleration were carried out. Frequency characteristics of suspension motion and regularities of vertical movement of the wheel were identified after dividing the investigated road section according to driving modes. The analysis into the wheel contact with the road surface and identified correlations enable to determine the vehicle stability on selected quality roads.First Published Online: 16 Dec 2014